Identifikasi Hama Dan Strategi Pengendalian Pada Perkebunan Kopi Arabika (Coffea arabika L.) Di Kecamatan Naman Teran Kabupaten Karo - Prastio, Bayu; Setiawan, Andi; Warsito, Kabul (Mahesa Research Center, 2025)
The high incidence of pest attacks in coffee plantations has led to a decline in both the productivity and quality of coffee. As an initial step in addressing this issue, it is essential to collect data on the types of pests that attack coffee plantations in a particular area. This study aimed to identify pest species and determine appropriate control strategies in Arabica coffee (Coffea arabica L.) plantations in Sigarang-garang Village, Naman Teran Subdistrict. Pest observation was conducted using the random sampling method, and the data were analyzed descriptively. The results showed that the main pests found in the coffee plantations of Sigarang-garang Village included the coffee berry borer (Hypothenemus hampei), coffee branch borer (Xylosandrus spp.), and green scale insect (Coccus viridis). Effective pest control requires several specific measures, including the application of pesticides, regular pruning, and crop rotation.